Sinus bradycardia is associated with poor outcome in critically ill patients with COVID-19 due to the B.1.1.7 Lineage. (2021) - Chalkias, Athanasios; Pantazopoulos, Ioannis; Papagiannakis, Nikolaos; Skoulakis, Anargyros; Laou, Eleni; Kolonia, Konstantina; Ntalarizou, Nicoletta; Tourlakopoulos, Konstantinos; Pagonis, Athanasios; Kampolis, Christos; De Guadiana Romualdo, Luis García; Ragias, Dimitrios; et al.
Graphical abstract: Highlights: A clinical marker associated with disease progression in patients with the B.1.1.7 Lineage would be extremely valuable. In this study, the majority of patients who developed sinus bradycardia during hospitalization were admitted to the ICU. Bradycardia was associated with the severity of the disease (p < 0.001) and outcome (p < 0.001). Bradycardia may be an early predictor of poor outcome in patients with severe COVID-19 due to the B.1.1.7 variant strain. Abstract: The progress of COVID-19 from moderate to severe may be precipitous, while the characteristics of the disease are heterogenous. The aim of this study was to describe the development of sinus bradycardia in critically ill patients with COVID-19 and its association with outcome in outbreak due to the SARS-CoV-2 B.1.1.7 Lineage. We leveraged the multi-center SuPAR in Adult Patients With COVID-19 (SPARCOL) study and identified patients who required admission to intensive care unit (ICU). Inclusion criteria were: (a) adult (≥18 years old) patients hospitalized primarily for COVID-19; (b) a confirmed SARS-CoV-2 infection diagnosed through reverse transcriptase polymerase chain reaction test of nasopharyngeal or oropharyngeal samples; and (c) at least one blood sample collected at admission and stored for suPAR, hs-CRP, and ferritin testing. All patients had continuous heart rate monitoring during hospitalization. In total, 81 patients were included. Of them, 17 (21 %) and 64 (79 %) were intubated and admitted to the ICU during the first and second wave, respectively. Two (12 %) and 62 (97 %) developed bradycardia before ICU admission, respectively (p < 0.001). Patients with bradycardia had increased suPAR (p < 0.001) and hs-CRP level (p < 0.001). Infusion of isoprenaline and/or noradrenaline was necessary to maintain an adequate rate and peripheral perfusion in all patients. Mortality was significantly higher in patients with bradycardia (p < 0.001). In conclusion, bradycardia was associated with poor outcome. As B.1.1.7 variant strain is spreading more rapidly in many countries, our findings help in the identification of patients who may require early admission to ICU.